Integrating Nationalism Values Through Al-Islam and Kemuhammadiyahan in High School Education Based on the Merdeka Curriculum - Firdaus; Muntohar; Hermawan (Journal of Educational Management Research, 2026)
This study aims to examine the implementation model and strategies for internalizing nationalistic values through the Al-Islam and Kemuhammadiyahan (AIK) curriculum in line with the Merdeka Curriculum’s goal of shaping faithful, devout, and leadership-oriented students. A qualitative field research method was employed, involving key informants such as school leaders and AIK teachers. The findings reveal the use of the Three Pillars of Ideological Integration Model, which effectively embeds nationalism into the formal AIK curriculum, non-formal student organization activities, and overall school culture. The primary strategy identified was identity synchronization, achieved by aligning AIK content with the Pancasila Student Profile (P5) framework of the Merdeka Curriculum. The model successfully fosters Amaliyah Nationalism (practical nationalism) based on Islam Wasathiyyah (Moderate Islam), framing contribution to the nation as an act of worship. Strong institutional ideology serves as a key supporting factor, while exposure to unchecked digital information represents a significant challenge. These findings provide a practical framework for integrating moral, religious, and nationalistic values in secondary education and suggest strategies for enhancing student character development in contemporary curricula. *